Socio-Demographic Analysis of Children in Child Care Homes in Nepal - Ghimire, Nabin Chandra (Kutumbha vani, 2023)
The Nepali government established the National Council for Child Rights in 2018 to ensure children’s rights and monitors 548 Child Care Homes (CCHs) in 46 districts. A study aims to explore the socio-demographic status of children in CCHs, identifying trends and demographic differences. Attachment theory, developed by John Bowlby, highlights the distress children experience when separated from their parents. Over 2.7 million children aged 0-17 live in care institutions globally, with 120 per 100,000 children. Factors like HIV/AIDS, natural disasters, and cultural differences influence placement. The National Plan Commission aims to make high-income countries responsible donors and participants in development. The study investigates child care home management and children’s rights in 63 Nepalese Child Care Homes (CCHs) using a mixed model of qualitative and quantitative methods. Results show 47.1% are boys and 52.9% are girls, with the majority under 5 years old. Out of 2,121 children, 72.0% are orphans. Nepal’s child care home numbers are decreasing due to government policies, with girls more likely to stay. Non-orphan children remain, with 72% double orphans, predominantly from Hindu families. The Nepali government should collaborate with nongovernmental organizations and academic institutions to develop a national child protection system.